Fatores associados ao óbito e à reposição volêmica em pacientes com trauma por lesões penetrantes - Márcia Cristine Pires Travassos; Isabel Cristina Bandeira da Silva; João Paulo Bessa de Lima; Celso Martins Fonseca; Jacqueline de Almeida Gonçalves Sachett; Sibila Lilian Osis (Universidade Federal do Ceará, 2016)
Objective: to evaluate the prognostic factors of volume replacement in patients with trauma due to penetrating injuries. Methods: retrospective cohort study whose data were obtained by analyzing medical records of 544 patients who were admitted to the emergency unit, victims of penetrating trauma. Results: among the victims, 282 (51.9%) suffered stab wound, 262 (48.2%) injury by firearms, 486 (89.3%) were male, 382 (70.2%) were aged between 14 and 30 years. Most who received volume greater than 2000ml, systolic blood pressure ≤90mmHg and mean arterial pressure ≤65mmHg presented more mortality, with p <0.05, p <0.002 and p <0.003, respectively. Conclusion: the limited volume replacement can help in the good prognosis of victims of penetrating trauma.